2D Modeling for Structural Flood Mitigation and Normalization with HEC-RAS: A Case Study of Tabelo River - Agastya, Dewandha Mas; Kusuma, Rr. Widyawati Tresna; Jayanegara, I Dewa Gede; Yasa, I Wayan; Sulistiyono, Heri (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2025)
Changes in land use for the development of the Mandalika Special Economic Zone (SEZ) have led to increased flooding. A rainfall intensity of 35 mm recorded at the ARR KEK Mandalika station led to a flood event, with a water level reaching 1.2 meters on March 23, 2022. Therefore, a study is needed to determine the flood discharge that affects the Tabelo Watershed and to identify the appropriate structural mitigation measures for flood management. After conducting frequency analysis with Hydrognomon and Generalized Extreme Value (GEV), the flood discharge for the 50, 100, and 200-year return periods was 149.5 m3/s, 162.5 m3/s, and 175.2 m3/s. Structural mitigation by river normalization and levees construction on the Tabelo River was carried out along 1882.5 m at stationing P0 – P101 and 468.5 m at stationing S0 – S30. The levee construction is planned to be 14 m wide for the upstream section, up to the junction, and 16 m wide for the junction to the river mouth. The river levee is designed to be 3.30 meters high and 16 meters wide. The stability of the levee is calculated by considering its stability against overturning, sliding, and reactions from the foundation soil under both normal and seismic conditions. Based on the results of the stability calculations, the safety factor values for stability against shear forces under normal and earthquake conditions were obtained, namely, Fs (3.81 > 2.00) and Fs (1.27 > 1.25).